Edukasi Konsep Bank Sampah dan Uang Beredar Kepada Pekerja di Bank Sampah Berkah Kecamatan Medan Belawan - Rangkuty, Dewi Mahrani; Suryani Sajar; Rahmadhani Fitri; Naibaho, Yanti Br (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The purpose of this community service is to educate the concept of Waste Bank, Green Economy, and Circulating Money to the community in Medan Belawan District. The specific target in this community service is that the Berkah Waste Bank workers in Medan Belawan Subdistrict know what Waste Bank, Green Economy, and Money Circulating to the Community in Medan Belawan Subdistrict, how to apply them to become household income opportunities, for example by becoming a new source of income from saving household waste that has been applied so that they can read the economic and environmental problems that occur. The materials presented in this community service are: what is a Waste Bank, Green Economy, and Circulating Money, how the impact of the Waste Bank on income from household waste. Which is related to improving household welfare through community knowledge / understanding related to Waste Bank, Green Economy, and Circulating Money. From this community service, the results show that with the existence of the Waste Bank, the application of the Green Economy concept can be seen from the collection of household waste easily collected at the Waste Bank, the community becomes a customer, has savings, withdraws money, then continues consumption shopping from the money, which means there is buying and selling activity in the market because there is money circulating in the community. This affects economic activity in the Medan Belawan sub-district.